ROLE OF JOURNALISTS IN AWARENESS CAMPAIGN TOWARD SPECIAL EDUCATIONAL NEEDS CHILDREN AND THEIR CONSCIOUSNESS - Hafiz Rukhsar Ahmed, Quratulain Rizvi, (JIE, 2024)
The aim of the current study was to explore the awareness of journalists about disability and their role in creating awareness regarding disability. Journalists who are working for print media (Newspaper) and electronic media (News channel) in Sialkot and Lahore were the population of study. It was a cross sectional study, consisted of N=60 Journalists both male & female. Journalists were rated on a researcher made questionnaire which consisted of 33 items. The internal reliability of the instrument was found to be 0.91. It was concluded that journalists have comprehensive knowledge regarding all the disabilities except autism. It is recommended that Disability content should be included in masscommunication or journalism studies to make journalists a voice of persons with disabilities.